Association Between Social Media Use and Depression Among University Students - Sallehuddin, Hidayah; Sawai, Rezki Perdani; Abdul Aziz, Abdul Rashid; Kasmani, Mohd Faizal (‘Abqari Journal, 2021)
The most widely used social media such as Twitter, Instagram and Facebook have changed the way we communicate with others especially amongst youth. It has been a major part of such activities in their lives. However, the most alarming situation is that youth are mostly students. It has been identified that those who spent more time online have evidenced more symptoms of depression. On that note, this study concerns to (i) identify the level of depression and (ii) to find out the relationship between social media and depression among them who are among undergraduate students. In order to retrieve the data, a set of questionnaire was distributed to 150 students of local university in Malaysia, that consists of three sections which are demographic information, Social Media Addiction Scale-Student Form (SMAS-SF) and Beck Depression Inventory 2nd Edition (BDI-II). There were two variables analyzed using Pearson correlation test. In short, the result showed that there is a correlation between social media and depression, r=0.199, n=150, p=<0.01. From this finding, it depicts that social media is significantly related and have positive relationship to depression among students involved. This study also provides such valuable information for counsellors and lecturers to identify students who have suffered depression and could help them to manage the problem. It also creates awareness among parents to be more alert with their children’s emotion.